Risk assessment in medically treated chronic thromboembolic pulmonary hypertension patients - Delcroix, Marion; Stähler, Gerd; Tiede, Henning; Grünig, Ekkehard; Held, Matthias; Halank, Michael; Klose, Hans; Vonk-Noordegraaf, Anton; Rosenkranz, Stephan; Pepke-Zaba, Joanna; Opitz, Christian F. (The European respiratory journal, 2018)
Abbreviated versions of the ESC/ERS pulmonary hypertension guidelines risk stratification have been recently validated in patients with pulmonary arterial hypertension. We aimed to investigate their prognostic value in medically treated chronic thromboembolic pulmonary hypertension (CTEPH) patients from the COMPERA registry, which collects six variables of interest (WHO functional class, 6-minute walking distance, brain natriuretic peptide, right atrial pressure, cardiac index and mixed venous oxygen saturation). - We included patients with at least one follow-up visit, no pulmonary endarterectomy, and at least three of the six variables available, and classified the patients into low, intermediate and high risk groups. As secondary analysis, the number of non-invasive low risk criteria was counted. The association between risk assessment and survival was evaluated. - Data from inclusion and follow-up (median, 7 months) visits were available for 561 and 231 patients, respectively. Baseline 1- and 5-year survival estimates were significantly different (p<0.0001) in the baseline low (98.6;88.3%), intermediate (94.9;61.8%), and high risk (75.5;32.9%) cohorts. Follow-up data were even more discriminative with, respectively, 100, 92 and 69% 1-year survival. The number of low risk non-invasive criteria was also associated with survival. - These analyses suggest that the ESC/ERS risk assessment may be applicable in patients with medically treated CTEPH.